FAKTOR-FAKTOR YANG MEMPENGARUHI EFEKTIVITAS PENERIMAAN PAJAK BEA BALIK NAMA KENDARAAN BERMOTOR PROVINSI BALI - Ardina Natasya, Ida Ayu; Ery Setiawan, Putu (E-Jurnal Akuntansi, 2016)
One source of revenue is to be improved for financing the delivery of government and regional development of Bali Province as an autonomous region is BBNKB taxes. The purpose of this study was to determine the influence of public services, competence human resources, and taxpayer compliance of the effectiveness of tax revenue BBNKB Bali Province. Method of determining the sample in this study was done by using cluster sampling or sampling area. Respondents in this research were 100 taxpayers BBNKB obtained by using Slovin formula. This study tested using multiple linear regression analysis using SPSS. Based on the results of the analysis can be concluded that the public service variables significant positive effect on the effectiveness of tax revenue BBNKB, the competence of human resources has positive influence on the effectiveness of tax revenue and tax compliance BBNKB positive influence on the effectiveness of tax revenue BBNKB Bali Province.
Keywords: Public Service, Human Resource Competency Apparatus and Taxpayer Compliance, Effectiveness Tax Revenue